Protocol standardization may improve precision error of InBody 720 body composition analysis - Herberts, T.; Slater, G. J.; Farley, A.; Hogarth, L.; Areta, J. L.; Paulsen, G.; Garthe, I. (International Journal of Sport Nutrition and Exercise Metabolism, 2023)
Background: Bioelectrical impedance analysis (BIA) is a popular technique which can be used to track longitudinal changes in body composition. However, precision of the technique has been questioned, especially among athletic populations where small but meaningful changes are often observed. Guidelines exist which attempt to optimize precision of the technique but fail to account for potentially important variables. Standardization of dietary intake and physical activity in the 24 hr prior to assessment has been proposed as an approach to minimizing the error of impedance-derived estimates of body composition. Methods: Eighteen recreational athletes, male (n = 10) and female (n = 8), underwent two consecutive BIA tests to quantify within-day error, and a third test (the day before or after) to quantify between-day error. All food and fluid intake plus physical activity from the 24 hr prior to the first BIA scan was replicated during the following 24 hr. Precision error was calculated as the root mean square standard deviation, percentage coefficient of variation, and least significant change. Results: There were no significant differences in precision error of within- and between-day fat-free mass, fat mass, and total body water. Differences in precision error of fat-free mass and total body water, but not fat mass, were less than the smallest effect size of interest. Conclusion: The 24-hr standardization of dietary intake and physical activity may be an effective approach to minimizing precision error associated with BIA. However, further research to confirm the validity of this protocol compared to nonstandardized or randomized intake is warranted.